Blastability Classification of Fractured Rock Mass Based on Weighted Clustering Analysis - Tiejun Tao; Ping Huang; Jianmin Zhou; Hongbing Yu; Jie Li (Chemical Engineering Transactions, 2017)
This paper classifies the blastability of fractured rock mass based on the solid coefficient, rock impedance, unit explosive consumption and mean fracture spacing. Specifically, an evaluation model was established according to the principle of clustering analysis, and applied to classify the rock mass blastability of an actual project. According to the field acoustic test, the average longitudinal wave velocity of the layered rock mass is 2,667m/s, and that of the intact rock mass is 3,346m/s. Through the evaluation of blastability, it is concluded that the layered rock mass has a high blastability while the intact rock mass has a medium blastability. The findings lay an important theoretical basis for blasting parameters optimization and field blasting test.